Geological constraints for a conceptual evolutionary model of the slope deformations affecting Mt. Nuovo at Ischia (Italy) - Esposito, Carlo; Della Seta, Marta; Marmoni, Gian Marco; Martino, Salvatore; Paciello, Antonella; Perinelli, Cristina; Sottili, Gianluca (Italian journal of engineering geology and environment, 2015)
Ischia Island was the scenario of several Holocene slope instability events occurred at different scales, from shallow mass movements, triggered by meteo-climatic forcing, up to massive rock slope failures such as large debris avalanches these last ones related to the volcano-tectonic dynamics of a resurgent caldera. The present study focuses on the gravitational deformation that involves Mt. Nuovo, located in the western portion of Mt. Epomeo resurgent block. A high-resolution engineering-geological model was reconstructed according to a multi-modelling approach supported by field geo-structural evidences and constrained by passive seismic investigations. It revealed a complex morpho-structural setting and led to the identification of a multiple compound mechanism, involving a rock mass volume of about 190 million of cubic meters. The obtained geological model shows a partial structural control of the pre-existing tectonic pattern on slope deformation mechanisms, highlighting geometric and volumetric similarities between the Mt. Nuovo ongoing deformation and an already occurred rock avalanche. The defined conceptual evolutionary model allows to hypothesize the role of inner pressures constraining the shear zone initiation and propagation and making reliable a future scenario of generalized collapse. Starting from these new field and laboratory data, numerical models will be reconstructed in order to depict the evolution of the gravitational slope deformation, evaluate its sensitivity and constrain future evolutionary instability scenarios.